The Philosophy and Foundations of Vocational Technology in Education with IT Integration - Nasution, Malinar; Jalinus, Nizwardi (Hanif Journal of Information Systems, 2024)
The development of Information Technology (IT) has had a significant impact on vocational education in this modern era. This article aims to explore the relationship between philosophy and the foundations of vocational technology with curriculum development, teaching methods, and evaluation in the educational context. The main focus is on the importance of understanding the philosophical underpinnings of vocational technology and how philosophy can guide the implementation of information technology in vocational education. Through this analysis, it is hoped that new ways can be found to enrich students' learning experiences and prepare them for future challenges in a workforce increasingly intertwined with technology.